2015
DOI: 10.1039/c5an01404b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring silver ionic liquids for reaction-based gas sensing on a quartz crystal microbalance

Abstract: Reaction-based, sensitive sensing of aldehyde and ketone gases in real time was effectively achieved on QCM chips thin-coated with silver ionic liquids and , respectively. The method platform developed in this work involves straightforward synthesis of functional silver ionic liquids in water, and is label-free and highly chemoselective with superior gas reactivity for and and, most significantly, totally insensitive to moisture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It is of note that this optimized synthesis of ionic liquids 1 and 2, in our hands required no chromatographic separation. In our research, we are interested in developing new ionic liquids or improving the synthesis of known ionic liquids and we have an ongoing program to evaluate ionic liquids as stable media for chemical synthesis [7][8][9][10][11] and as functional materials for biochemical applications [12,13]. We recently reported the preparation of bicyclic 1,2,3-triazolium ionic liquids in four steps with good yields [1].…”
Section: Resultsmentioning
confidence: 99%
“…It is of note that this optimized synthesis of ionic liquids 1 and 2, in our hands required no chromatographic separation. In our research, we are interested in developing new ionic liquids or improving the synthesis of known ionic liquids and we have an ongoing program to evaluate ionic liquids as stable media for chemical synthesis [7][8][9][10][11] and as functional materials for biochemical applications [12,13]. We recently reported the preparation of bicyclic 1,2,3-triazolium ionic liquids in four steps with good yields [1].…”
Section: Resultsmentioning
confidence: 99%
“…The PVD techniques are more environmentally friendly than traditional coating methods, with several applications from scientific and industrial points of view.Infact, thin films produced by PVD are being developed and applied in electrical and semiconductor manufactories, for example, in organic electronics and optoelectronics (OLEDs, OPVs, OFETs), andu sed for energy conservation and/or generation. [26][27][28] The trend shifts observed fort he thermodynamic properties of vaporization of the [C n C 1 im][Ntf 2 ] IL series, which occur at [C 6 C 1 im][Ntf 2 ]( the CAS, or criticala lkyl size), are evidenceo ft he nanostructuration of ILs. [21] High-accuracyv apor-pressure data for the extended[ C n C 1 im] [Ntf 2 ]i onic liquid series were determined by Santos et al by using aK nudsen effusion apparatus combined with aQ CM and the authors contributed for ab etter understanding of the relationship between cohesive energies, volatilities, and liquid structures of ILs.…”
mentioning
confidence: 99%
“…[25] Recently,t here have been other groups who have startedu sing aQ CM and PVD to measure vapor pressures of ILs and prepare ultrathin IL films by using vapor deposition techniques. [26][27][28] The trend shifts observed fort he thermodynamic properties of vaporization of the [C n C 1 im][Ntf 2 ] IL series, which occur at [C 6 C 1 im][Ntf 2 ]( the CAS, or criticala lkyl size), are evidenceo ft he nanostructuration of ILs. Another important contribution,p resented by Coutinho et al,h as shown that the surface tension of this class of ionic liquidsd ecreases with an increase in the cation alkyl side chain size up to aliphatic chains no longer than hexyl, labeled as the CAS.…”
mentioning
confidence: 99%
“…Since 2010, we have put in efforts to the development of a series of affinity ionic liquids (AILs) targeted specifically for chemoselective gas sensing [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Albeit the bulk reports from others in the past have been successful in detecting gas molecules via physical adsorption, the challenge for those methods remains for better specificity to discriminate structurally similar gas molecules from others.…”
Section: Ionic Liquid On Qcm For Chemoselective Gas Sensingmentioning
confidence: 99%